Les médecins aux bords de leurs savoirs - Thomas Bujon; Christine Dourlens (Revue d'anthropologie des connaissances)
When doctors operate on the margins of their jurisdiction and are faced with challenges that do not fall strictly within the pathological framework, they are called to deal with situations that medical knowledge cannot always adequately address. Collegial decision-making procedures can then offer a means to pool their uncertainty and alleviate the lack of scientific support or moral foundation upon which they would usually rely. This article comes from a study conducted in a hospital-based multidisciplinary committee focused on the medical care of trans individuals. The remit of the committee is to make medical decisions where there are controversies and uncertainties. This article shows how the decisions made in this committee are not based exclusively on medical criteria but also bring in to play political and moral standards. If through their successive decisions, doctors change the framework they had originally constructed and applied, thereby setting up new norms, they do this not by creating new knowledge, new definitions, or new standards, but by highlighting the fragility of existing standards and constituted knowledge.